Social Media Intervention and Substantive Justice Crisis: A Critical Legal Theory Study of Decision 726/Pid.Sus/2023/PN PIg - Sherlin Lovina Manalu; Indah Sri Utari (Universitas Negeri Semarang, 2026)
Social media has influenced criminal justice processes through the formation of public opinion that may exert pressure on objectivity and independence of law enforcement and judicial institutions. This condition has contributed to a crisis of substantive justice, in which legal proceedings are increasingly shaped by social pressure rather than by principles of procedural justice. This article aims to analyze social media intervention in the criminal justice system using the perspective of Critical Legal Theory. Socio-legal approach implememt by combining normative legal analysis with empirical examination of judicial practices in the digital era. The study shows social media pressure can undermine judicial impartiality, limit the discretion of law enforcement officials, and weaken the legitimacy of judicial institutions. This study concludes that institutional strengthening and legal reconstruction are necessary to preserve judicial independence, protect human rights, and ensure the realization of substantive justice.